Characterization of Prostaglandin F2α Receptors in Human Eyelids. Issue 2 (March 2015) - Nesher, Ronit; Mimouni, Michael; Elnaddaf, Halah; Nemet, Arie; Kidron, Debora
Purpose: Elongation, thickening, and crowding of eyelashes are commonly seen after topical use of prostaglandin analog eyedrops for glaucoma treatment. The purpose of this study was to demonstrate the presence and characterize the location of prostaglandin analog F2α receptors (PGF2α ) in human hair follicles. Methods: In this observational clinical laboratory study, excised eyelid specimens following eyelid surgery were studied. Resected portions of eyelids were submitted for histopathologic evaluation. For immunohistochemistry evaluation, a polyclonal antibody directed against PGF2α was purchased from Cayman Chemical. The staining procedure was carried out on an automatic stainer. Results: Out of 26 patients recruited, final analysis was conducted on 17 eyes of 15 patients. There were 10 men and 5 women (mean age 77 ± 14 years). Staining was detected only in hair follicles in the anagen stage (37 slices). No variation in pattern, distribution, or intensity of immunostaining was noted among sections of different individuals. Only the bulb and stem of the hair follicle stained positive. In the bulb, the strongest staining occurred in the matricular cells and in the inner sheath layer. In the stem, the strongest staining occurred in the Huxley layer of the inner sheath. Conclusions: This immunohistologic study found that PGF2α receptors were located predominantly in the inner root sheath of the bulb and stem of eyelashes and expressed only in eyelashes in the anagen phase.